2006
DOI: 10.1111/j.1365-2222.2006.02453.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of profilin and lipid transfer protein in strawberry allergy in the Mediterranean area

Abstract: In addition to a Bet v 1 homologue, strawberry also contains IgE-binding profilin and LTP. The rFra a 3 has less allergenic potency than peach and apple LTP, and therefore is an interesting tool for future immunotherapy. Fra a 3 does not seem to be clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 37 publications
(39 reference statements)
3
40
0
Order By: Relevance
“…The results are in concordance with a stronger biological potency reported for Pru p 3 in comparison to nsLTP from strawberry [20] and plane pollen [13]. Although all tested patients reported adverse reaction to hazelnut and Cor a 8-specific IgE was at least 5.6 kU A /l (CAP class 3), only 2 patients showed a moderate in vitro histamine release induced by Cor a 8.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The results are in concordance with a stronger biological potency reported for Pru p 3 in comparison to nsLTP from strawberry [20] and plane pollen [13]. Although all tested patients reported adverse reaction to hazelnut and Cor a 8-specific IgE was at least 5.6 kU A /l (CAP class 3), only 2 patients showed a moderate in vitro histamine release induced by Cor a 8.…”
Section: Discussionsupporting
confidence: 77%
“…Cross-reactivity between Pru p 3 and food nsLTPs from taxonomically distantly related plant species was assessed in previous studies either by using extracts containing unknown amounts of nsLTP and/or mainly in a semi-quantitative manner by immunoblotting inhibition experiments [20,21,24,26,27,28]. In the present study, experimental conditions were clearly defined, as purified and structurally characterized allergen molecules were used in dose-dependent assays, allowing a quantitative evaluation of data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corecognition between strawberry pollen and strawberry juice is, however, conceivable. Zuidmeer et al [32 ]demonstrated that strawberry also contains allergens with high molecular weights (20–28, 40–80 kDa). …”
Section: Discussionmentioning
confidence: 99%
“…The same protocol was used for RAST inhibitions, with a 2-hour pre-incubation of 50 µl of serum with 50 µl of inhibitor diluted in PBS/AT (0.3% BSA and 0.2% Tween, pH 7.4) before the addition of Sepharose-coupled allergen. For grape LTP inhibition, 8-fold serial dilutions of extracts (initial concentrations 5 mg/ml) from grape, peach, apple, hazelnut, olive pollen, Parietaria and peanut or purified natural (n) or recombinant (r) grape (nVit v 1), strawberry (rFra a 3) [15], hazelnut (nCor a 8) [unpubl. data], maize (nZea m 14) [16], sunflower (nHel a 3) [17] or wheat rLTP [18] used at a concentration of 50 µg/ml.…”
Section: Methodsmentioning
confidence: 99%